Outcomes of Extracorporeal Membrane Oxygenation in COVID-19–Induced Acute Respiratory Distress Syndrome: An Inverse Probability Weighted Analysis. (7th October 2022) - Raasveld, Senta Jorinde; Taccone, Fabio Silvio; Broman, Lars Mikael; Hermans, Greet; Meersseman, Philippe; Quintana Diaz, Manuel; Delnoij, Thijs S. R.; van de Poll, Marcel; Gouvea Bogossian, Elisa; van Baarle, Floor L. F.; Durak, Koray; Zayat, Rashad; et al.
Abstract : IMPORTANCE: Although venovenous extracorporeal membrane oxygenation (VV ECMO) has been used in case of COVID-19 induced acute respiratory distress syndrome (ARDS), outcomes and criteria for its application should be evaluated. OBJECTIVES: To describe patient characteristics and outcomes in patients receiving VV ECMO due to COVID-19–induced ARDS and to assess the possible impact of COVID-19 on mortality. DESIGN, SETTING AND PARTICIPANTS: Multicenter retrospective study in 15 ICUs worldwide. All adult patients (> 18 yr) were included if they received VV ECMO with ARDS as main indication. Two groups were created: a COVID-19 cohort from March 2020 to December 2020 and a "control" non-COVID ARDS cohort from January 2018 to July 2019. MAIN OUTCOMES AND MEASURES: Collected data consisted of patient demographics, baseline variables, ECMO characteristics, and patient outcomes. The primary outcome was 60-day mortality. Secondary outcomes included patient characteristics, COVID-19–related therapies before and during ECMO and complication rate. To assess the influence of COVID-19 on mortality, inverse probability weighted (IPW) analyses were used to correct for predefined confounding variables. RESULTS: A total of 193 patients with COVID-19 received VV ECMO. The main indication for VV ECMO consisted of refractory hypoxemia, either isolated or combined with refractory hypercapnia. Complications with the highest occurrence rate included hemorrhage, an additional infectious event or acute kidney injury. Mortality was 35% and 45% at 28 and 60 days, respectively. Those mortality rates did not differ between the first and second waves of COVID-19 in 2020. Furthermore, 60-day mortality was equal between patients with COVID-19 and non-COVID-19–associated ARDS receiving VV ECMO (hazard ratio 60-d mortality, 1.27; 95% CI, 0.82–1.98; p = 0.30). CONCLUSIONS AND RELEVANCE: Mortality for patients with COVID-19 who received VV ECMO was similar to that reported in other COVID-19 cohorts, although no differences were found between the first and second waves regarding mortality. In addition, after IPW, mortality was independent of the etiology of ARDS.